2014
DOI: 10.1017/s0047279414000221
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about Social Fluidity and Preferences for Social Policies

Abstract: Several studies have shown that attitudes toward social policy are influenced by expectations of social mobility at the individual level and perceptions of social fluidity at the aggregate level. If individuals think of inequalities as the result of inherited disadvantages, they will be more willing to distribute resources from the rich to the poor. However, one important question remains open: How do individuals perceive the distribution of opportunities in society? In this paper we argue that individuals bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…For instance, Brown‐Iannuzzi, Lundberg, Kay, and Payne (2015) showed that experimentally manipulated subjective status was negatively related to attitudes towards redistribution even in cases when participants could not profit from holding such attitudes in the particular experimental game, and studies including perceptions of life‐long and contextual risks show that even prospects of upward mobility lead members of lower classes to reject redistribution (Bénabou & Ok, 2001; Cojocaru, 2014). Furthermore, individuals may operate with inaccurate data, whether in regard to estimates of actual differences in wealth and incomes (Kelley & Zagorski, 2004; Norton & Ariely, 2011), potential for social mobility (Jaime‐Castillo & Marqués‐Perales, 2014; Kraus & Tan, 2015), or performance of the welfare state (van Oorschot & Meuleman, 2012). Finally, people may also have skewed perceptions of both the actual structure and of realistically attainable and desirable alternatives (e.g., relative deprivation; Evans & Kelley, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For instance, Brown‐Iannuzzi, Lundberg, Kay, and Payne (2015) showed that experimentally manipulated subjective status was negatively related to attitudes towards redistribution even in cases when participants could not profit from holding such attitudes in the particular experimental game, and studies including perceptions of life‐long and contextual risks show that even prospects of upward mobility lead members of lower classes to reject redistribution (Bénabou & Ok, 2001; Cojocaru, 2014). Furthermore, individuals may operate with inaccurate data, whether in regard to estimates of actual differences in wealth and incomes (Kelley & Zagorski, 2004; Norton & Ariely, 2011), potential for social mobility (Jaime‐Castillo & Marqués‐Perales, 2014; Kraus & Tan, 2015), or performance of the welfare state (van Oorschot & Meuleman, 2012). Finally, people may also have skewed perceptions of both the actual structure and of realistically attainable and desirable alternatives (e.g., relative deprivation; Evans & Kelley, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Recently, psychologists have shown that just as people are inaccurate in their inequality estimates, they are similarly ignorant of how rigidly immobile their country is (Davidai & Gilovich, 2015; Kraus & Tan, 2015). Recent work by economists and political scientists has shown correlations between levels of mobility and support for redistributive policies such that the more mobile the society, the less support there is for governmental efforts such as increasing taxation on the rich (e.g., Alesina & La Ferrara, 2005; Bjørnskov, Dreher, Fischer, Schnellenbach, & Gehring, 2013; Dabalen, Parinduri, & Paul, 2015; Jaime-Castillo & Marqués-Perales, 2014). However, none of these studies examine how perceptions of income mobility influence attitudes about income inequality.…”
mentioning
confidence: 99%
“…The social‐psychological foundations of beliefs about inequality are particularly important in this regard (Kaufman, ). Various recent studies in social psychology, social policy and sociology suggest that perceived level of inequality of opportunity is associated with preferences for redistributive policies (Jaime‐Castillo & Mareques‐Perales, ; Kim, Huh, Choi, & Lee, ; Shariff, Wiwad, & Aknin, ). The main mechanism underpinning this link is that when individuals perceive that everyone gets a fair chance to succeed in life, then redistributive policies should be limited because a talent‐ and effort‐based meritocracy is an appropriate method of distributing resources (Alesina & Giuliano, ; Kluegel & Smith, ).…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Previous studies, using various data sets and research designs, have investigated the consequences of intergenerational mobility in individuals' objective characteristics on support for redistribution. While some scholars' findings suggest that upward mobility is negatively associated with redistribution preferences (Alesina & La Ferrara, ; Jaime‐Castillo & Mareques‐Perales, ; Siedler & Sonnenberg, ), others have found no, or even positive, associations between the two (Clark & D'Angelo, ; Gugushvili, ; Guillaud, ).…”
mentioning
confidence: 99%